The peach seed - Jones, Anita Gail (Henry Holt and Company, 2023)
"On a routine trip to the Piggly Wiggly in Albany, Georgia, widower Fletcher Dukes smells a familiar perfume, then sees a tall woman the color of papershell pecans with a strawberry birthmark on the nape of her neck. He knows immediately that she is his lost love, Altovise Benson. Their bond, built on county fairs, sit-ins, and marches, once seemed a sure and forever thing. But their marriage plans were disrupted when the police turned a peaceful protest violent. Before Altovise fled the South, Fletcher gave her a peach seed monkey with diamond eyes. As we learn via harrowing flashbacks, an enslaved ancestor on the coast of South Carolina carved the first peach seed, a talisman that, ever since, each father has gifted his son on his thirteenth birthday. Giving one to Altovise initiated a break in tradition, irrevocably shaping the lives of generations of Dukeses. Recently, Fletcher has made do on his seven acres with his daughter Florida's check-ins, his drop biscuits, and his faithful dog. But as he begins to reckon with long-ago choices, he finds he isn't the only one burdened with unspoken truths. An indelible portrait of a family, The Peach Seed explores how kin pass down legacies of sorrow, joy, and strength. And it is a parable of how a glimmer of hope as small as a seed can ripple across generations"--